2015
DOI: 10.1002/jsfa.7085
|View full text |Cite
|
Sign up to set email alerts
|

Processing barley grain with lactic acid and tannic acid ameliorates rumen microbial fermentation and degradation of dietary fibre in vitro

Abstract: Chemical and heat treatment of barley grain modulated the ruminal fermentation profile and enhanced fibre degradation; however, processing of grain with LA seems to be superior because this effect was not associated with a concomitant depression in ruminal degradation of organic matter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
64
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(70 citation statements)
references
References 40 publications
3
64
3
Order By: Relevance
“…Additionally, iso-VFAs might increase digestibility of nutrients (especially dry matter) and microbial population in ruminal fluid (Miltko et al, 2016). This difference could be explained by amino acid degradation of dietary crude protein, since amino acids are protected by bacteria associated with rumen protozoa (Deckardt et al, 2016). In the present study, the increased protozoan abundance was observed after the highest dose of boric acid was added into diet, which could result in the reduction of ammonia utilizing bacteria.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Additionally, iso-VFAs might increase digestibility of nutrients (especially dry matter) and microbial population in ruminal fluid (Miltko et al, 2016). This difference could be explained by amino acid degradation of dietary crude protein, since amino acids are protected by bacteria associated with rumen protozoa (Deckardt et al, 2016). In the present study, the increased protozoan abundance was observed after the highest dose of boric acid was added into diet, which could result in the reduction of ammonia utilizing bacteria.…”
Section: Discussionmentioning
confidence: 51%
“…The basal diet used in the present study was a high forage ration, and any changes in VFA profile could be attributed to the interaction of lactate utilizing bacteria with acetate-propionate utilizing bacteria. Lactate is rapidly converted into propionate, n-butyrate, n-valerate and caproate in the rumen by lactate utilizing bacteria that use acetate as a co-factor, leading to diverse concentrations of acetate and propionate (Mao et al, 2008;Deckardt et al, 2016). Our data showed that the increasing concentration of boron altered the VFA profile in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 71%
“…The addition of citric acid to barley grain would contribute to maintain a higher and more stable pH in the rumen. It has been shown that treating barley grain with LA or tannic acid caused changes in the ruminal microbiota improving fibre digestibility (Deckardt et al, 2016). Harder et al (2015c) reported an increase in the abundance of Prevotella bacteria and enhanced fibre degradation in vitro when barley was treated with citric acid.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing ruminally resistant starch (RRS) in cereal grains by chemical treatments would preclude a rapid fermentation of starch in the forestomachs (Deckardt et al, 2016), thus enhancing the post-ruminal absorption and the net hepatic uptake of glucose, which can be utilised more efficiently than VFA. One alternative chemical treatment to increase RRS is the addition of organic acids (Deckardt et al, 2016) to cereal grains.…”
mentioning
confidence: 99%
See 1 more Smart Citation